UN Peacekeeping Operations and Economic Growth -A study of UN's Peacekeeping Operations since 1948 - Rehncrona,Carin (2008)
The study aims at exploring the links between peacekeeping operations and economic growth. The paper examines the countries in which past United Nations Peacekeeping Operations have been present and calculates the growth rates before, after and during each operation. Comparisons of the growth rates are made to show how the operation has affected the economic growth in the country. It is also discussed in what way a peacekeeping operation can affect economic growth. This includes creating a more stable environment and prospects of peace, which in turn makes the country more attractive for investments. Other factors generated by the mission that can be good for the economy includes more job opportunities for the community, and that the expenditures by mission personnel in the country creates more flow of money and can thereby enhance the production. The empirical result shows that the peacekeeping operations affect the growth rate in a positive way on an aggregate level, when the operation is in progress as well as after it is completed. The operations after the end of the Cold War have a more immediate effect on growth, compared to the ones that took place before the war, they proved to have more of a long-term effect.
Keywords: economic growth; Peacekeeping; United Nations; Economics, econometrics, economic theory, economic systems, economic policy; Nationalekonomi, ekonometri, ekonomisk teori, ekonomiska system, ekonomisk politik